AB0325 Biomarkers and Patient Tailored Approach in Rheumatoid Arthritis: Can Proms be the Missing Biomarker?. (9th June 2015) - El Miedany, Y.; El Gaafary, M.; Youssef, S.; Palmer, D.
Abstract : Background: In many chronic diseases, there is usually a single "gold standard" biomarker measure which is applicable to diagnosis, management, prognosis, and analyses of outcomes in all individual patients in clinical trials, clinical care, and long-term databases (such as blood pressure in hypertension, and HbA1c in diabetes). In contrast, in most rheumatic diseases, there is none. This absence of a gold standard measure resulted in the suggestion of pooled indices, which are complex, and used in clinical trials but not in clinical care. Objectives: To assess the feasibility of using PROMs and its individual components as a valid biomarker enabling the treating doctor to optimally measure disease progression, severity and joint damage in patients with inflammatory arthritis. Methods: Changes from baseline to week 76 of clinical variables, patient reported outcome measures [1], and measures of radiographic progression were assessed in 481 subjects suffering from early inflammatory arthritis (Disease duration <6-months) diagnosed according to the ACR/EULAR criteria 2010 and treated to Target. Radiographic progression was scored at baseline and at 76-weeks using modified Sharp score as well as US scores for number of erosions, synovial hypertrophy and vascularity (using Power Doppler). Biochemical laboratory measures included ESR, CRP and rheumatoid factor. Correlation of changes in PROMs individual components scores to response to therapy at 3, 6 and 12 months of management as well as to work ability, development of erosions and joint affection were studied. The sensitivity and specificity of Functional disability as an indicator of prognosis was also assessed using ROC curve analysis. Linear regression analysis was used to assess the significance of correlations for changes in disease activity and PROMs components over time. Results: The crude functional disability score as well as the percentage changes at 3 and 6 months showed a significant increase in the group with persistent inflammatory synovitis compared to the self-limiting arthritis group. Using binary logistic regression analyses to assess the association between functional disability and disease activity flare up revealed that a flare was associated with poor baseline function and quality of life measures: Functional disability [OR per 0.1 unit=1.8 (1.06–1.54), p=0.004] and Quality of Life [OR=1.12 (1.01–1.23), p=0.024]. Patient global assessment and pain score were associated significantly with scores of DAS-28, ACR response, systemic manifestations and work ability. Changes in the functional disability scores correlated significantly to changes in PD scores (p<0.01). In multiple conditional logistic regression analysis, factors associated with the development of joint space narrowing were worsening of functional disability score by >0.5/3, synovial thickening and synovial PD score ≥2 at both baseline and 6-months of treatment. The discriminative power had an AUC of 0.864 (95% CI 0.765 - 0.937), with Sensitivity 84%, Specificity 92% and LR + 5.6. Conclusions: PROMs met the criteria of a valid marker for rheumatoid arthritis, being objectively measured, indicator of normal and pathologic joint affection, as well as a sensitive and specific marker for response to therapy and poor prognosis. References: El Miedany et al. Clin Exp Rheumatol 2010; 28: 734. Disclosure of Interest: None declared